2021
DOI: 10.3390/jcs5080196
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Filler Morphology on the Electrical and Thermal Conductivity of PP/Carbon-Based Nanocomposites

Abstract: In this paper, we studied the effect of different carbon-based nanostructures on the electrical and mechanical properties of polypropylene (PP) nanocomposites. Multi-walled carbon nanotubes (MWCNT), expanded graphite (EG), and two different carbon black nanoparticles (CB) have been dispersed at several weight contents in the polymer matrix through a melt extrusion process. The produced nanocomposites have been used to obtain samples for the characterization by injection molding. The dispersion of the nanoparti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
2
0
1
Order By: Relevance
“…In recent years, the progress of materials science and electronic technologies in the field of multifunctional sensing devices has allowed the development of smart solutions for monitoring civil structures and safeguarding of the safety of their users during their service lives [1,2]. In particular, novel promising fillers with enhanced properties are available in the market, and several researchers are investigating their potentialities [3][4][5]. In the field of engineering, carbon-based particles are very interesting because of their various applications [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the progress of materials science and electronic technologies in the field of multifunctional sensing devices has allowed the development of smart solutions for monitoring civil structures and safeguarding of the safety of their users during their service lives [1,2]. In particular, novel promising fillers with enhanced properties are available in the market, and several researchers are investigating their potentialities [3][4][5]. In the field of engineering, carbon-based particles are very interesting because of their various applications [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…As for the electrical conductivity of nanoelastoplastic, here the main role in increasing the value of this indicator is played by TC nanoparticles. 21 The loading of 20 wt% TC nanoparticles promotes the formation of TPE nanocomposite and the formation of chain electronic conductivity, in which the electrical conductivity is 10 −3 (ohm⋅m) −1 . At the same time, it was found that the load of only 5.0–7.0 wt % TC into the composition of the initial HDPE leads to the formation of a nanocomposite with electrical conductivity within 10 −2 (ohm⋅m) −1 .…”
Section: Results and Its Discussionmentioning
confidence: 99%
“…В данной статье основное внимание уделяется разработке высококристаллического полиэтилена высокой плотности (ПЭВП) и исследованию электропроводящих полимерных нанокомпозитов на его основе с использованием различных типов углеродсодержащих наполнителей: техуглерода и графита. Несмотря на большое число работ в этой области, отсутствие системного подхода к исследованию влияния углеродных наполнителей на закономерность изменения электропроводности и свойств нанокомпозитов до сегодняшнего дня не позволяет разработать новые научные подходы для интерпретации механизма цепочечной проводимости [12][13][14]. Многие авторы объясняют это обстоятельство тем, что исследования в этой области носят в ряде случаев противоречивый характер, не позволяющий в совокупности выработать единую цельную теорию по оценке электропроводности композитных материалов [15][16][17][18].…”
unclassified